An Arabidopsis Cytokinin-Modifying Glycosyltransferase UGT76C2 Improves Drought and Salt Tolerance in Rice - Li, Yanjie; Liu, Fangfei; Li, Pan; Wang, Ting; Zheng, Chengchao; Hou, Bingkai (Frontiers in Plant Science, 2020)
Drought and salt stresses are common environmental threats that negatively affect rice development and yield. Here we report that the overexpression of AtUGT76C2, a cytokinin glycosyltransferase, in rice modulates cytokinin homeostasis and confers the plants an eminent property in drought and salt tolerance. The transgenic plants exhibit sensitivity to salt and drought stress as well as abscisic acid during the germination stage and the postgermination stage while showing enhanced tolerance to drought and salinity at the young seedling stage and the mature stage. The overexpression of UGT76C2 decreases the endogenous cytokinin level and enhances root growth, which greatly contributes to stress adaptation. In addition, the transgenic plants also show enhanced ROS scavenging activity, reduced ion leakage under salt stress, smaller stomatal opening, and more proline and soluble sugar accumulation, which demonstrate that UGT76C2 acts as an important player in abiotic stress response in rice. To explore the molecular mechanism of UGT76C2 in response to stress adaptation, the expressions of eight stress-responsive genes including OsSOS1, OsPIP2.1, OsDREB2A, OsCOIN, OsABF2, OsRAB16, OsP5CR, and OsP5CS1 were detected, which showed notable upregulation in UGT76C2 overexpression plants under salt and drought stresses. Our results reveal that the ectopic expression of AtUGT76C2 confers the transgenic rice many traits in improving drought and salt stress tolerance in both developmental and physiological levels. It is believed that AtUGT76C2 could be a promising candidate gene for cultivating saline- and drought-tolerant rice.